Investigation of the Enrichment and Accumulation of Normal Pressure Shale Gas in Anchang Syncline Outside of Sichuan Basin - Lan, Baofeng; Zhao, Fuping; Li, Shaopeng; Jiang, Haishen; Liu, Song; Zhang, Zhiyao (Frontiers in Earth Science, 2022)
Gas shales from the Wufeng-Longmaxi Formation in Anchang syncline in northern Guizhou area of Sichuan Basin are stable in distribution and can be classified as type I shale gas reservoir with great resource potential. The exploration and development of shale gas in Anchang syncline have achieved great progress. However, the enrichment rule and accumulation pattern of shale gas in Anchang syncline are still not clear at the present. Gas pressure in the Wufeng-Longmaxi Formations shales in Anchang syncline is normal. The maximum tested gas production in the field ranges from 18,000 to 58,000 m3/d. However, gas production of shale wells varies greatly even in the same platform. In order to understand the shale gas enrichment and accumulation and improve the effective development of shale gas in this area, comparative analyses on the geological characteristics and preservation conditions of gas reservoirs in several typical wells were carried out from the perspective of geology, petrophysics, geophysics, and well logging. Results show that shale gas in Anchang syncline has the characteristics of accumulating in both deep central position and gently wings. Tectonic preservation condition is the key factor to high gas production in Anchang area. The hydrological conditions, syncline structure, fault distribution, and cap rock quality comprehensively control the gas pressure and gas bearing capacity of shale reservoir. According to these factors, an accumulation model of shales with normal gas pressure is established: syncline controls the distribution of gas reservoir; fault controls the boundary of the reservoir; preservation conditions controls gas capacity. The results are benefit for the rolling exploration and development of shale gas in Anchang area, and are important for the development of normal pressure shale gas in northern Guizhou area.